1991
DOI: 10.1002/app.1991.070420525
|View full text |Cite
|
Sign up to set email alerts
|

Mooney scorch time of epoxidized natural rubber

Abstract: SYNOPSISThe scorch property of accelerated sulfur vulcanization of three grades of epoxidized natural rubber (viz. ENR 10, ENR 25, and ENR 50) was studied by using Mooney Shearing Disk Viscometer in the temperature range of 10O-18O0C. Effects of accelerator types, concentration of accelerator, and carbon black on ENR 10 were also determined. Results obtained indicate a similar scorch behavior as that reported earlier for SMR L. However, some differences in the magnitude of scorch times in the temperature and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 12 publications
2
30
0
1
Order By: Relevance
“…Furthermore, the increased thermal conductivity of rubber compounds by the addition of CB [17–19] and the reactive organic groups (such as phenolic, hydroxyl, quinone, carboxyl) and reactive hydrogen bonds, as well as free radicals on the surface of CB, can also react chemically with the rubber molecules [13, 16], which has the potential to promote the kinetics of the crosslinking reaction. This phenomenon was also identified by previous studies [20–25]. On the other hand, the rubber compound filled with SiO 2 has an increase in t 90 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the increased thermal conductivity of rubber compounds by the addition of CB [17–19] and the reactive organic groups (such as phenolic, hydroxyl, quinone, carboxyl) and reactive hydrogen bonds, as well as free radicals on the surface of CB, can also react chemically with the rubber molecules [13, 16], which has the potential to promote the kinetics of the crosslinking reaction. This phenomenon was also identified by previous studies [20–25]. On the other hand, the rubber compound filled with SiO 2 has an increase in t 90 .…”
Section: Resultssupporting
confidence: 86%
“…This is attributed to the greater amount of accelerators (with respect to sulfur), which leads to a more effective use of the sulfur as to attain a satisfactory degree of cure [16]. It is also found that the t scorch and t 90 particularly decrease with increased cure temperatures, as a consequence of the available thermal energy to overcome the activation energy of the cure process [20], while the increase of temperature does not bring about any major changes in the minimum torque or stock viscosity of the compounds. As indicated in literatures [13, 16, 21–23], the torque difference (Δ M ) generally relates to the degree of crosslinking; the rubber compound vulcanized by the CV system is found to be much higher than that of the EV system.…”
Section: Resultsmentioning
confidence: 99%
“…Technical specification of the ENR 25 was given in our previous report. 8 Zinc oxide, coumarone-indene resin, and toluene were used as the filler, tackifier, and solvent, respectively, in this research. All the materials used in this experiment were freshly supplied commercial grades.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…It can be seen that for a similar type of filler, the t 90 of SMR L/ENR 25 blends is shorter than that of SMR L/SBR blends. We have reported15 that, due to the activation of the adjacent double bond by the epoxide group in ENR, the scorch time and cure time are shorter than that of SMR L. However, SBR, which has fewer double bonds, as discussed before, cures more slowly than SMR L and thus the t 90 of SMR L/ENR 25 blends is shorter than that of SMR L/SBR blends.…”
Section: Resultsmentioning
confidence: 83%